Effect of carbonated drinks on wound healing of oral epithelium - Ayesha Fahim; Muhammad Sharjeel Ilyas; Fahim Haider Jafari; Fauzia Farzana (Elsevier, 2016)
Background: Carbonated drinks are the second most consumed non-alcoholic beverages in the world after tea. The effects of these drinks on hard tissues and vital organs of the body have been proved beyond doubt. This study, however, explains the effect of these drinks on wound healing of oral epithelium. Methods: Thirty-six male Wistar rats were considered for the study. A circular wound of 3.0 mm was created on the buccal mucosa of all animals and they were divided into two groups. Animals in group 1 were fed with chow pellet and water, while those in group 2 were fed with a commercially available carbonated drink instead of water. Six animals from each group were euthanized at 0, 7, and 21 days. Wound site was histologically assessed for differences in thickness and characteristics of the regenerating epithelium between two groups. Results: There was a marked difference in the healing pattern between the two groups. Animals in group 1 showed a normal healing pattern at the end of day 21. In the group 2, the regenerated epithelium showed hyperplasia and hyperkeratosis along with acanthosis at the end of the experiment with a subsequent delayed inflammatory reaction at day 21. Conclusion: Consumption of carbonated drinks can disrupt oral wound healing. The contents in carbonated drinks have a proinflammatory action on the soft tissue. Results suggest that epithelial changes seen in experimental group 2 could be a result of constant irritation by the acidic and fizzy nature of carbonated drinks.